Isolation and identification of antagonistic fungi for biocontrol of Impatiens hawkeri leaf spot disease and their growth-promoting potential - Li, Huali; Yang, Mingguo; Liu, Jian; Sun, Yajiao; Yang, Huajun; Lu, Junjia (Frontiers in Microbiology, 2025)
Impatiens hawkeri, a plant of great horticultural significance with high ornamental and economic value, is frequently afflicted by leaf spot disease caused by Stagonosporopsis cucurbitacearum, and effective biological control methods for this disease are yet to be fully explored. To address this issue, the plate confrontation method was used to isolate five antagonistic fungal strains from Quercus spinosa, which showed strong inhibitory effects against S. cucurbitacearum with inhibition rates of 53.12% for CG6, 43.42% for CG7, 68.13% for CY12, 54.30% for CJ18, and 67.23% for CJ19, respectively. Among them, strain CY12 demonstrated the highest antifungal activity, significantly suppressing the mycelial growth of S. cucurbitacearum. Through morphological observation and sequence analyses of ITS, TEF, and RPB2, CY12 was identified as Fusarium solani. Further experiments revealed that CY12 could produce cell wall hydrolases and exhibited multiple growth-promoting properties, such as phosphorus and potassium solubilization, nitrogen fixation, and indoleacetic acid (IAA) production, and it also produced various cell wall-degrading enzymes like amylase, cellulase, and β-glucanase. Additionally, CY12 showed strong antagonistic effects against six common ornamental plant pathogens, with an inhibition rate of 71.41% against the pathogen causing Rhododendron leaf spot disease. Pot experiments indicated that CY12 effectively reduced the occurrence of leaf spot disease on I. hawkeri plants, increased the seed germination rate from 93% in the control group to 98.33%, and promoted seedling growth. These results suggest that the endophytic fungus CY12 has strong antifungal and growth-promoting properties, providing potential strain resources for the biological control of leaf spot disease in I. hawkeri and the development of fungal fertilizers, and further exploration of its field application effects and action mechanisms is necessary.